Effect of constructive rehybridization on transverse conductivity of aligned single-walled carbon nanotube films. Issue 9 (November 2018) - Chen, Mingguang; Li, Wangxiang; da Silveira Venzel, Thaís Eloá; Li, Guanghui; Itkis, Mikhail E.; Haddon, Robert C.; Bekyarova, Elena
Graphical abstract: Abstract: Alignment of densely packed single-walled carbon nanotubes (SWNTs) largely preserves the extraordinary electronic properties of individual SWNTs in the alignment direction, while in transverse direction the films are very resistive due to large energy barriers for tunneling between adjacent SWNTs. We demonstrate that chromium atoms inserted between the sidewalls of parallel SWNTs effectively coordinate to the benzene rings of the nanotubes via hexahapto bonds that preserve the nanotube-conjugated electronic structure and serve as a conduit for electron transfer. The atomically interconnected aligned SWNTs exhibit enhanced transverse conductivity, which increases by ∼2100% as a result of the photoactivated organometallic functionalization with Cr. The hexahapto mode of bonding the graphitic surfaces of carbon nanotubes with transition metal atoms offers an attractive route to the reversible chemical engineering of the transport properties of aligned carbon nanotube thin films. We demonstrate that a device fabricated with aligned SWNTs can be reversibly switched between a state of high electrical conductivity (ON) by light and low electrical conductivity (OFF) by applied potential. This study provides a route to the design of novel nanomaterials for applications in electrical atomic switches, optoelectronic and spintronic devices.